Outcomes in elderly patients undergoing endovascular thrombectomy in association with premorbid Rankin Scale scores - Ippen, Franziska M.; Schregel, Katharina; Ungerer, Matthias; Feisst, Manuel; Ringleb, Peter A.; Gumbinger, Christoph K. (Frontiers in Neurology, 2024)
Background Endovascular thrombectomy (EVT) reduces disability in patients with acute ischemic stroke (AIS); however, its efficacy in patients aged >80 years remains unclear. Objectives This study aimed to assess the impact of premorbid modified Rankin Scale (pmRS) scores and age on patients with AIS undergoing EVT and the effect of EVT on functional outcome and mortality. Methods We conducted a retrospective cohort study and screened the Heidelberg Recanalization Registry (HeiReKa) database for patients with AIS between 1999 and 2021. Outcomes were stratified by age (<80, 80–89, and ≥90 years) and pmRS score (0–2 vs. 3–5). Adjusted odds ratios for outcomes and mortality at 3 months after treatment were examined. Results Finally, 2,591 patients were included [including those aged ≥90 years (n = 158)]. Poor functional outcomes were associated with advanced age, vascular risk factors, stroke severity, and vessel status. Conversely, lower prestroke disability and younger age were associated with better outcomes and reduced mortality. A pmRS of 3–5 was associated with an increased risk of mortality and worse functional outcomes regardless of age. Notably, patients aged ≥90 years with a pmRS of 0–2 had significantly better outcomes than those aged <80 years with a pmRS of 3–5. Conclusion Both age and pmRS are important in assessing the benefits of EVT. However, prestroke functional status might be more crucial than biological age in determining outcomes following EVT.